Low-gas-emission red phosphorus flame-retardant reinforced PA66 composite material and preparation method thereof

CN122917532APending Publication Date: 2026-10-16ZHEJIANG YONGXING PLASTIC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611280369.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-22
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

增加包覆层会降低有效磷含量,需提高红磷添加量,反而可能加剧热降解;降低加工温度则牺牲了PA66的结晶度与力学强度,难以兼顾高温加工低产气、力学性能保持、长期电性能稳定的三项需求

Benefits of technology

本发明提供的低产气量红磷阻燃增强PA66复合材料及其制备方法,通过采用含硼酚醛树脂与硅烷偶联剂对红磷进行协同表面改性,并创新性地引入经特定表面修饰的纳米氮化硼作为“热管理-物理阻隔”双功能中心,结合可选的金属钝化、结晶调控、反应型阻燃增效及陶瓷化协效等多种手段,实现了显著降低加工产气量,改善加工环境与安全性,有效保持并优化了材料的力学性能与尺寸稳定性,大幅提升了材料在长期热湿老化环境下的电绝缘性能保持率,确保了极端工况下的使用可靠性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material and a preparation method thereof, which comprises the following components in parts of mass: PA66 resin 55-68 parts; surface modified red phosphorus 4.5-5.5 parts; the surface modified red phosphorus is coated red phosphorus modified by silane coupling agent KH550; chopped glass fiber 20-35 parts; antioxidant 0.3-0.5 parts; lubricant 0.3-0.5 parts; surface modified boron nitride 1-3 parts; the surface modified boron nitride is nanoscale boron nitride modified by octadecylamine; gas generation during processing is inhibited, and the final obtained material has excellent mechanical properties and maintains long-term electrical property stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to red phosphorus flame-retardant polymer materials, and in particular to low-gas-yield red phosphorus flame-retardant reinforced PA66 composite materials. Background Technology

[0002] Polyamide 66 engineering plastics are widely used in electronics, electrical engineering, new energy vehicles, and rail transportation due to their excellent mechanical properties, heat resistance, and electrical insulation. In these applications, materials typically need to meet high flame retardant ratings (such as UL94V-0). Red phosphorus, with its high phosphorus content, low addition amount, and good flame retardant efficiency, has become an important choice for high-end halogen-free flame-retardant PA66 systems.

[0003] However, existing red phosphorus flame-retardant reinforced PA66 composite materials face three prominent technical challenges in industrialization: First, red phosphorus is prone to thermal oxidation during the high-temperature (typically 240-260℃) melting process of PA66, generating large amounts of phosphorus oxide fumes and highly toxic phosphine gas, which not only harms the working environment and corrodes equipment but also leads to poor product appearance. Second, the oxidation process of red phosphorus causes chain breakage and cross-linking of the PA66 matrix molecular chains, resulting in a significant decrease in the material's impact strength and large fluctuations in melt flow rate, severely affecting the stability and batch consistency of precision injection molding. Finally, existing red phosphorus coatings (such as melamine-formaldehyde resin coatings) may fail under long-term hot and humid aging conditions, leading to a continuous deterioration in electrical insulation properties such as tracking index (CTI), failing to meet the stringent long-term reliability requirements of components such as battery pack housings for new energy vehicles.

[0004] Existing technologies mainly alleviate gas generation problems by increasing the thickness of the red phosphorus coating, adding auxiliary antioxidants, or lowering the processing temperature, but these approaches often come at the expense of other aspects. Increasing the coating reduces the effective phosphorus content, requiring an increase in the amount of red phosphorus added, which may exacerbate thermal degradation. Lowering the processing temperature sacrifices the crystallinity and mechanical strength of PA66, making it difficult to simultaneously meet the three requirements of low gas generation during high-temperature processing, maintenance of mechanical properties, and long-term stable electrical properties. Summary of the Invention

[0005] To address the technical challenges of high gas production, deterioration of mechanical properties, and unstable long-term electrical insulation performance in traditional red phosphorus flame-retardant PA66 materials during processing, a low-gas-production red phosphorus flame-retardant reinforced PA66 composite material and its preparation method are provided.

[0006] The above-mentioned objective of this invention is achieved through the following technical solutions: A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material comprises the following components by mass parts: 55-68 parts of PA66 resin; 4.5-5.5 parts of surface-modified red phosphorus; the surface-modified red phosphorus is coated red phosphorus modified with silane coupling agent KH550; 20-35 parts chopped glass fiber; Antioxidant 0.3-0.5 parts; 0.3-0.5 parts lubricant; 1-3 parts of surface-modified boron nitride; the surface-modified boron nitride is nano-sized boron nitride modified with octadecylamine.

[0007] By adopting the above technical solution, KH550 is used to modify the surface of the coated red phosphorus to achieve physical isolation and inhibit its initial activity. Then, on this basis, nano boron nitride modified with octadecylamine is added. The surface-modified nano boron nitride serves as a multifunctional synergistic center, and at the same time plays a dual role as a "thermal conductor" and "barrier" for the surface-modified red phosphorus. During processing and heating, nano boron nitride, with its extremely high in-plane thermal conductivity, can quickly dissipate the "local hot spots" generated by the thermal oxidation of red phosphorus particles, suppressing the generation of gases such as phosphine from the thermodynamic source and avoiding the generation of gases such as phosphine during the processing and production process. When the material is used, the nano boron nitride is oriented in the PA66 matrix to form a dense physical barrier network, which effectively delays the penetration of external water vapor and oxygen into the interior and the migration of internal acidic degradation products, thereby protecting the interface between the red phosphorus coating layer and the PA66 matrix and forming long-term electrical insulation stability (high CTI value). In addition, antioxidants and lubricants ensure the thermal and oxygen stability of the matrix and the processing fluidity of the overall system, making the material production process more uniform and stable, and ensuring the stability of material performance. This achieves the suppression of gas generation during processing, while maintaining the excellent mechanical properties of the final material and preserving its long-term electrical stability.

[0008] Optionally, the coating layer is a boron-containing phenolic resin.

[0009] By adopting the above technical solution, boron-containing phenolic resin is used as the surface coating layer of red phosphorus. This coating layer forms a dense and stable physical barrier on the surface of red phosphorus particles, which can effectively block the direct contact between water vapor, oxygen and the core of red phosphorus, thereby significantly inhibiting the generation of phosphine gas caused by hydrolysis and oxidation of red phosphorus during storage, processing and use. Secondly, when the composite material is heated or burned, the boron-containing phenolic resin itself undergoes decomposition and cross-linking reactions to form borides, which promote the formation of a denser, continuous, and thermally stable expanded char layer. This char layer not only has excellent heat and material insulation functions, but can also further encapsulate and fix red phosphorus, inhibiting its further decomposition and gas production. Thus, it produces a significant flame-retardant synergistic effect with red phosphorus decomposition products, PA66 matrix, and boron nitride and other components, realizing a dual gas suppression mechanism of "physical sealing" and "chemical synergy", thereby improving the overall flame-retardant efficiency.

[0010] Optionally, it also contains 0.5-1.5 parts of β-cyclodextrin-encapsulated zinc borate, wherein the zinc borate is 4ZnO·B2O3·H2O (ZB-233 type), and the molar ratio of β-cyclodextrin to zinc borate is 1:1 to 1:2.

[0011] By adopting the above technical solution, β-cyclodextrin is added to include zinc borate (ZB-233 type). β-cyclodextrin forms a host-guest interaction with the B–O / Zn–O groups on the surface of zinc borate through its hydrophobic cavity. Partial borate oligomeric fragments on the surface of zinc borate enter the β-cyclodextrin cavity, and β-cyclodextrin is simultaneously adsorbed and assembled on the surface of zinc borate particles, forming a core-shell inclusion product. The host-guest interaction causes the β-cyclodextrin cavity to generate a polarization effect on the B–O bonds, lowering the dehydration temperature of zinc borate by 10–15℃ (to 245–250℃). The action of β-cyclodextrin-encapsulated zinc borate (ZB-233 type) in PA66 composite materials is divided into a processing stage and three heating stages based on the temperature window: Processing section (230-275℃): The dehydration initiation temperature of bare ZB-233 is about 260℃. After inclusion with β-cyclodextrin, the hydrophobic microenvironment of the cyclodextrin cavity polarizes the B–O bonds on the surface of zinc borate, reducing the dehydration activation energy. During the short dwell time of twin-screw extrusion, the partial dehydration conversion rate of the inclusion compound and the small amount of crystal water released are immediately absorbed by B2O3 (B2O3 + 3H2O → 2H3BO3). At the same time, ZnO reacts with the trace amount of free H3PO4 generated in the processing section (from the early hydrolysis of red phosphorus and the thermal oxidation of carboxylic acid by PA66) to generate Zn3(PO4)2. Therefore, the inclusion compound plays the role of "absorbing free water + removing free acid" in the processing section. Stage I: Using the thermal shock stage (200-260℃), when the temperature rises to approximately 245℃, the inclusion complex begins to gradually dehydrate, and ZnO and B2O3 are released into the matrix prematurely. ZnO preventively removes carboxylic acids produced by PA66 aging and free H3PO4 produced by early hydrolysis of red phosphorus, while B2O3 absorbs free water introduced by the product's hygroscopic process. At this stage, red phosphorus has not yet decomposed significantly, but the initiation conditions for the autocatalytic cycle (red phosphorus hydrolysis → H3PO4 production → catalytic further hydrolysis) have been weakened by ZnO and B2O3, thus blocking the establishment of the autocatalytic cycle. Stage II: The stage of massive decomposition of red phosphorus (260-320℃). The main dehydration peak of the inclusion complex is located at 260-275℃, which completely overlaps with the decomposition initiation temperature of red phosphorus (approximately 260℃) and the massive decomposition window. At this time, ZnO continues to react with the free H3PO4 overflowing from the matrix (3ZnO + 2H3PO4 → Zn3(PO4)2 + 3H2O), and B2O3 continues to absorb free water (B2O3 + 3H2O → 2H3BO3). At the same time, B2O3 can also react directly with H3PO4 to form the BPO4 ceramic phase. It is important to emphasize that ZnO only removes the free H3PO4 that overflows from the matrix (from the side reaction of red phosphorus hydrolysis and the hydrolysis of PA66 carboxylic acid, which is the driver of the autocatalytic cycle). The H3PO4 (P4→P2O5→H3PO4→polyphosphoric acid→char formation) used for the flame retardant main chain at the red phosphorus particle interface is located inside the red phosphorus coating layer and the polyphosphoric acid condensation reaction is self-sustaining and fast (millisecond level). ZnO has a low concentration at the interface and cannot intervene. Therefore, the condensed phase flame retardant main chain of red phosphorus is not affected. Similarly, B2O3 absorbs free water (PA66 hygroscopic water, processing residual water, and interface water), while the water sources required for red phosphorus flame retardancy—the structurally bound water generated by the amide bond breakage of PA66 at >300℃ (located at the chain break site, in a non-free state) and the reaction coordinate transition state water released by the polyphosphoric acid condensation reaction (generated inside the polyphosphoric acid chain segment and immediately consumed)—are different from the targets captured by B2O3 in terms of spatial location and existence form. B2O3 cannot contact or steal them. ZnO removes free H3PO4 overflowing from the matrix (a self-catalytic cycle driver), not the H3PO4 used for the flame-retardant backbone at the red phosphorus interface (the two have different spatial locations: the former is in the matrix, the latter is inside the red phosphorus coating layer). B2O3 absorbs free water (the source of water from red phosphorus hydrolysis), not the water from PA66 degradation or polyphosphoric acid condensation (the two exist in different forms: the former is free H2O molecules, the latter is structurally bound water or water in the reaction coordinate transition state, which B2O3 cannot access). Therefore, "acid removal + water absorption" is parallel to the condensed phase flame-retardant backbone of red phosphorus, and there is no conflict between "acid removal + water absorption" and the flame-retardant backbone of red phosphorus, and the product Zn3(PO4)2 / BPO4 is homologously fused with the phosphate carbon layer. (The inert Al2O3 decomposition product of existing ATH technology does not have this function.) Stage III: Combustion section (>350℃), after dehydration, ZnO, B2O3 and their reaction products Zn3(PO4)2 and BPO4 enter the carbon layer together, forming a homologous fused Zn-BP multi-element ceramic reinforced carbon layer with the red phosphoric acid carbon layer, further improving the density and thermal stability of the carbon layer.

[0012] This allows the release window of the dehydrated component (B2O3) to be precisely synchronized with the gas production window of red phosphorus (by including ZB-233, the dehydration initiation temperature is shifted from about 260℃ to 245-250℃, and the main peak overlaps with the decomposition window of red phosphorus).

[0013] The dehydrated product ZnO selectively removes the overflowing free H3PO4 (autocatalytic cycle driver) in the matrix without interfering with the flame-retardant intermediates at the red phosphorus interface; B2O3 selectively absorbs free water (the source of red phosphorus hydrolysis) without competing for PA66 degradation water and polyphosphoric acid condensation water (the two have different properties and positions); finally, without weakening the flame retardancy of the red phosphorus condensed phase, the autocatalytic cycle of red phosphorus hydrolysis is cut off, significantly reducing the amount of PH3 produced, while the ceramic phases such as Zn3(PO4)2 and BPO4 synergistically enhance the flame-retardant effect with the red phosphorus carbon layer.

[0014] Optionally, the mass ratio of the β-cyclodextrin-encapsulated zinc borate to the surface-modified boron nitride is 1:(1-2), and the mass ratio of the β-cyclodextrin to the surface-modified red phosphorus is 1:(3-6).

[0015] By adopting the above technical solution, the mass ratio of β-cyclodextrin-encapsulated zinc borate to surface-modified boron nitride is limited to 1:(1-2), and the mass ratio of β-cyclodextrin-encapsulated zinc borate to surface-modified red phosphorus is limited to 1:(3-6), so that the three key components achieve precise matching in terms of functional window and spatial distribution. Specifically, β-cyclodextrin-encapsulated zinc borate selectively removes free H3PO4 and B2O3 overflowing from the matrix and selectively absorbs free water through the dehydration product ZnO in the processing stage and at various temperature stages of use, thereby cutting off the autocatalytic cycle of red phosphorus hydrolysis; surface-modified boron nitride, with its extremely high in-plane thermal conductivity, rapidly dissipates local hot spots of red phosphorus particles and inhibits gas production from the thermodynamic source, while forming a physical barrier network in the matrix to delay the permeation of water vapor and oxygen. This ratio range ensures that the "acid-clearing and water-absorbing" effect of β-cyclodextrin-encapsulated zinc borate is neither antagonistic to the thermal barrier function of surface-modified boron nitride due to excess (for example, excessive ZnO may interfere with the directional arrangement of BN sheets or excessive consumption of acidic media in the matrix, leading to an imbalance of flame-retardant intermediates), nor insufficient to effectively inhibit the autocatalytic hydrolysis of red phosphorus. At the same time, the ratio of surface-modified boron nitride to surface-modified red phosphorus is just right so that the BN sheets can fully encapsulate the red phosphorus particles and match their particle size, maximizing heat dissipation and physical barrier.

[0016] Optionally, it may also include 0.2-1 parts of a nucleating agent, wherein the nucleating agent is zinc phenylphosphonate.

[0017] By adopting the above technical solution, to address the potential interference with the crystallization integrity of the PA66 matrix caused by the introduction of red phosphorus, glass fiber, and various fillers in this composite material system, zinc phenylphosphonate is added as a nucleating agent. This provides a large number of highly ordered heterogeneous nucleation sites during the cooling process of the PA66 melt, increasing the crystallization initiation temperature of PA66, accelerating the crystallization rate, and promoting a significant refinement and more uniform distribution of spherulites. Ultimately, PA66 constructs a more dense and complete crystal structure at the microscopic level, thereby improving the mechanical properties and long-term electrical stability of the composite material. In addition, the faster and more complete crystallization process reduces the residence time of the melt at high temperatures, indirectly reducing the time window for the thermal oxidation of red phosphorus and reducing subsequent gas production.

[0018] Optionally, it may also include 1-3 parts of low-melting-point glass powder, wherein the low-melting-point glass powder is borosilicate glass powder.

[0019] By adopting the above technical solution, during the melting production and processing of composite materials, the softening point of low melting point glass powder is higher than the processing temperature of PA66. Therefore, it is uniformly dispersed in the matrix in the form of stable solid particles, serving as a functional filler without melting and agglomeration. When the material is exposed to open flame, extreme high temperature environment or electric arc erosion, the temperature exceeds the softening point of the glass powder, causing the low melting point glass powder particles to soften and melt, and flow and spread on the surface of the material to form a continuous, dense glassy covering layer with ceramic properties. The capping layer acts as an excellent heat insulation and oxygen barrier in the condensed phase, significantly hindering the transfer of external heat to the interior of the matrix and the outward overflow of internal flammable pyrolysis products, thereby suppressing the continued combustion. On the other hand, its melt flow characteristics enable the capping layer to cover and fix any molten droplets that may be generated, improving flame retardant safety. Furthermore, the inorganic ceramic layer itself has extremely high insulation and arc resistance.

[0020] This suppresses smoke generation during combustion and significantly enhances the surface's resistance to arc erosion.

[0021] Optionally, the median particle size D50 of the surface-modified red phosphorus is 1.0 ± 0.05 μm.

[0022] By adopting the above technical solution, the size of the surface-modified red phosphorus is strictly controlled within an extremely narrow distribution range of 1.0±0.05μm. Its size is uniform and comparable to that of the nano-boron nitride sheets. It can achieve more uniform penetration and dispersion with the BN sheets during melt blending, avoiding functional phase separation or local enrichment caused by excessive particle size differences. This allows the thermal oxidation "hot spots" of the red phosphorus particles to be effectively covered and rapidly dissipated by the surrounding BN sheets with extremely high in-plane thermal conductivity, thereby maximizing the effect of nano-boron nitride, further reducing gas generation during production, and improving the material's processing performance and mechanical properties.

[0023] Optionally, the lubricant is ethylene bis-stearamide.

[0024] By adopting the above technical solution, ethylene bis-stearamide (EBS) has a good lubricating effect on the PA66 system with surface-modified red phosphorus and surface-modified boron nitride coexisting in this application, with a high melt extrusion molding rate and more stable product performance.

[0025] A method for preparing low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material includes the following steps: S1. Ingredients and premixing: Weigh each component according to the stated weight percentage, and mix all components in a high-speed mixer for 3-5 minutes to obtain a premix; S2. Melt blending and granulation: The premixed material is added to the main feed port of a twin-screw extruder, and the chopped glass fiber is added through the side feed port. The vacuum devolatilization device is turned on. After melt blending, extrusion, water cooling and pelletizing, composite material particles are obtained.

[0026] By adopting the above technical solution, in the melt blending stage of the twin-screw extruder, the high aspect ratio, specific speed and temperature settings jointly create a fluid environment with strong shear, high mixing and controllable thermal history, which promotes the full melting of PA66 resin and uses melt shear force to further peel off and disperse the surface-modified boron nitride, red phosphorus and other nano / micro fillers. At the same time, short glass fibers are added at the side feed port to maximize the maintenance of its aspect ratio and achieve effective reinforcement. Furthermore, during this process, vacuum devolatilization continuously removes trace amounts of moisture, low-molecular-weight volatiles, and trace amounts of gas remaining after red phosphorus inhibits oxidation, which may be generated due to material heating, thereby "solidifying" the effect of low gas production. A stable and high-performance low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material was obtained.

[0027] In summary, this application has at least the following beneficial effects: The present invention provides a low-gas-production red phosphorus flame-retardant reinforced PA66 composite material and its preparation method. By using boron-containing phenolic resin and silane coupling agent to synergistically modify the surface of red phosphorus, and innovatively introducing nano-boron nitride with specific surface modification as a dual-functional center of "thermal management-physical barrier", combined with optional metal passivation, crystallization control, reactive flame retardant enhancement and ceramicization synergy, it achieves a significant reduction in processing gas production, improves the processing environment and safety, effectively maintains and optimizes the mechanical properties and dimensional stability of the material, greatly improves the retention rate of electrical insulation performance under long-term hot and humid aging environment, and ensures the reliability of use under extreme working conditions. Detailed Implementation

[0028] raw material Red phosphorus micro powder, industrial grade high-purity red phosphorus, purity ≥99.5%, initial median particle size D50 is 1.5μm; Phenol, boric acid, anhydrous ethanol, N-methylpyrrolidone, N,N-dimethylformamide, and anhydrous diethyl ether were commercially available analytical grade products. Ammonia solution, a commercially available product, has a concentration of 26.4 wt%. Silane coupling agent KH550, active ingredient γ-aminopropyltriethoxysilane, commercially available product; Octadecylamine, a commercially available chemically pure product with a purity ≥98%; Paraformaldehyde, degree of polymerization n value of 12, analytical grade commercial product; PA66 resin, commercially available product, grade: EPR27; Short-cut glass fiber, commercially available alkali-free glass fiber specifically for nylon, with a single filament diameter of 11μm; Hindered phenolic antioxidant 1098 and phosphite antioxidant 168 are commercially available products. Ethylene bis-stearamide (EBS) is a commercially available product. Low melting point glass powder, which is borosilicate glass powder, with a softening point of 380℃; Melamine is a chemically pure commercially available product with a purity of ≥99%. N,N'-Bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine, a commercially available product of Guangzhou Yuanda New Materials Co., Ltd., CAS No. 32687-78-8, main content ≥98%, volatile matter ≤0.5%; Zinc phenylphosphonate, a commercially available product of Hefei Tianjian Chemical Co., Ltd., CAS No. 34335-10-9; Oxidized polyethylene wax, OPEW-OA9, a commercially available product from Anhui Kale New Materials Co., Ltd. Boron nitride nanosheets, in sheet form, with a size of 1-3μm, a purity of 99.9%, and an average thickness of less than 100nm, are commercially available products from Zhongke Leiming (Beijing) Technology Co., Ltd. β-Cyclodextrin, CAS No. 7585-39-9, molecular formula C 42 H 70 O 35 Molecular weight 1134.98, commercially available chemically pure product; ZB-233 type zinc borate, 4ZnO·B2O3·H2O, is a low-hydrated zinc borate, white powder, with a decrystallization temperature of about 415℃, a commercially available chemically pure product. Zinc borate FB-320 (2ZnO·3B2O3·3.5H2O, CAS No. 12767-90-7), molecular weight 434.68, commercially available chemically pure product.

[0029] Preparation Example 1 A surface-modified boron nitride is prepared as follows: Take 20g of boron nitride nanosheets and add them to 4000ml of N-methylpyrrolidone. Stir to form a mixed suspension. Centrifuge the resulting suspension at 3000rpm for 30min and collect the clear liquid of boron nitride nanosheets dispersed in the upper layer. The collected supernatant was further centrifuged at 12000 rpm for 30 min, the supernatant was discarded, and nanosheet precipitate was obtained. The precipitate was washed three times each with anhydrous ethanol and deionized water, and the washed precipitate was dispersed in 2000 ml of anhydrous ethanol to obtain boron nitride nanosheet ethanol dispersion. The boron nitride nanosheet ethanol dispersion was transferred to a reactor, and 60g of octadecylamine was added. High-purity nitrogen was introduced to replace the air while continuously stirring, and an inert atmosphere with slight positive pressure was maintained. The temperature was raised to 85℃, and the reaction was stirred and refluxed at this temperature for 18h. After the reaction was completed, heating was stopped, and the reaction system was allowed to cool naturally to room temperature. The reaction product was transferred to a centrifuge tube and centrifuged at 12000rpm for 20min. The solid was collected. The solid product was washed repeatedly with hot anhydrous ethanol at 60℃ at least five times until the washing liquid was colorless and transparent and no chloride ions were detected by silver nitrate solution (to ensure complete removal of unreacted octadecylamine and byproducts). The final washed solid product was placed in a vacuum drying oven and dried at 70℃ for 12h to obtain surface-modified boron nitride.

[0030] Preparation Example 2 A type of boron nitride nanoparticle, the preparation process of which is as follows: Take 20g of boron nitride nanosheets and add them to 4000ml of N-methylpyrrolidone. Stir to form a mixed suspension. Centrifuge the resulting suspension at 3000rpm for 30min and collect the clear liquid of boron nitride nanosheets dispersed in the upper layer. The collected supernatant was further centrifuged at 12,000 rpm for 30 min, and the supernatant was discarded to obtain nanosheet precipitate. The precipitate was washed three times each with anhydrous ethanol and deionized water, and the washed precipitate was dried at 70 °C for 12 h to obtain boron nitride nanoparticles.

[0031] Preparation Example 3 A surface-modified red phosphorus is prepared by the following steps: Add 100g phenol, 120g paraformaldehyde, 8g boric acid and 150g water to the reactor, stir evenly, and then adjust the pH of the solution to 8.0 with ammonia water. Then raise the temperature to 70℃ and keep the reaction at this temperature for 2 hours to obtain an aqueous solution of boron-containing phenolic resin prepolymer. In another reactor, 100g of red phosphorus powder and 500g of deionized water were added and stirred at 1000rpm to disperse the mixture evenly. The temperature was raised to 65℃, and boron-containing phenolic resin prepolymer aqueous solution was slowly added dropwise over a period of 45min while stirring continuously. After the addition was completed, the pH of the reaction system was maintained at 8.2 with ammonia water, and the reaction was continued at 75℃ for 4h. After the reaction was completed, heating was stopped, and the mixture was allowed to cool naturally to room temperature to obtain a crude intermediate. The crude intermediate was filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH=7). The filter cake was dried to obtain the boron-containing phenolic resin-coated red phosphorus intermediate. 100g of boron-containing phenolic resin-coated red phosphorus intermediate was dispersed in 400g of anhydrous ethanol and sonicated for 30min to ensure full dispersion. 5g of silane coupling agent KH550 was added to the suspension and stirred until homogeneous. The mixture was then transferred to a reaction flask equipped with a reflux condenser and heated to 78℃. The mixture was stirred and reacted at this temperature for 6h. After the reaction, the product was cooled, filtered, and washed three times with anhydrous ethanol to remove the physically adsorbed coupling agent. The resulting solid was then vacuum-dried at 80°C for 10 hours. Finally, the dried powder was precisely classified using an air classifier, and powder with a median particle size D50 of 1.02 μm was collected to obtain surface-modified red phosphorus. Chemical analysis of samples showed that the content of amino groups grafted onto the surface corresponded to a grafting rate of 0.9 mmol / g.

[0032] Preparation Example 4 A surface-modified red phosphorus is prepared by the following steps: Add 100g phenol, 120g paraformaldehyde, 8g boric acid and 150g water to the reactor, stir evenly, and then adjust the pH of the solution to 8.0 with ammonia water. Then raise the temperature to 70℃ and keep the reaction at this temperature for 2 hours to obtain an aqueous solution of boron-containing phenolic resin prepolymer. In another reactor, 100g of red phosphorus powder and 500g of deionized water were added and stirred at 1000rpm to disperse the mixture evenly. The temperature was raised to 65℃, and boron-containing phenolic resin prepolymer aqueous solution was slowly added dropwise over a period of 45min while stirring continuously. After the addition was completed, the pH of the reaction system was maintained at 8.2 with ammonia water, and the reaction was continued at 75℃ for 4h. After the reaction was completed, heating was stopped, and the mixture was allowed to cool naturally to room temperature to obtain a crude intermediate. The crude intermediate was filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH=7). The filter cake was then dried to obtain the boron-containing phenolic resin-coated red phosphorus intermediate. In this preparation example, the coating rate was determined by thermogravimetric analysis (TGA) to be 34.8 wt%. 100g of boron-containing phenolic resin-coated red phosphorus intermediate was dispersed in 400g of anhydrous ethanol, sonicated for 30min to ensure full dispersion, filtered, and washed three times with anhydrous ethanol to remove physically adsorbed coupling agent. The resulting solid was vacuum dried at 80℃ for 10h. Finally, the dried powder was precisely classified using an air classifier, and powder with a median particle size D50 of 1.0±0.05μm was collected to obtain surface-modified red phosphorus.

[0033] Preparation Example 5 A surface-modified red phosphorus is prepared by the following steps: 126g of melamine, 180g of paraformaldehyde (equivalent to 6mol of formaldehyde) and 300g of deionized water were added to the reactor. After stirring, the pH of the solution was adjusted to 8.5 with ammonia water. The temperature was raised to 75℃ and the reaction was kept at this temperature for 2 hours to obtain an aqueous solution of melamine-formaldehyde resin prepolymer. In another reactor, 100g of red phosphorus powder and 500g of deionized water were added and stirred at 1000rpm to disperse the mixture evenly. The temperature was raised to 65℃, and melamine-formaldehyde resin prepolymer aqueous solution was slowly added dropwise over a period of 55min while stirring continuously. After the addition was completed, the pH of the reaction system was maintained at 8.7 with ammonia water, and the reaction was continued at 75℃ for 4h. After the reaction was completed, heating was stopped, and the mixture was allowed to cool naturally to room temperature to obtain a crude intermediate. The crude intermediate was filtered, and the filter cake was repeatedly washed with deionized water until the filtrate was neutral (pH=7). The filter cake was dried to obtain the boron-containing phenolic resin-coated red phosphorus intermediate. 100g of boron-containing phenolic resin-coated red phosphorus intermediate was dispersed in 400g of anhydrous ethanol and sonicated for 30min to ensure full dispersion. 5g of silane coupling agent KH550 was added to the suspension and stirred until homogeneous. The mixture was then transferred to a reaction flask equipped with a reflux condenser and heated to 78℃. The mixture was stirred and reacted at this temperature for 6h. After the reaction was completed, the product was cooled, filtered, and washed three times with anhydrous ethanol to remove the physically adsorbed coupling agent. The resulting solid was vacuum dried at 80°C for 10 h. Finally, the dried powder was precisely classified using an air classifier, and the powder with a median particle size D50 of 1.02 μm was collected to obtain surface-modified red phosphorus.

[0034] Preparation Example 6 A surface-modified red phosphorus differs from preparation example 3 in post-treatment and product grading, as detailed below: After the reaction was completed, the product was cooled, filtered, and washed three times with anhydrous ethanol to remove the physically adsorbed coupling agent. The resulting solid was vacuum dried at 80°C for 10 h. Finally, the dried powder was precisely classified using an air classifier, and the powder with a median particle size D50 of 0.6 μm was collected to obtain surface-modified red phosphorus.

[0035] Preparation Example 7 A surface-modified red phosphorus differs from Preparation Example 3 in S5. Post-treatment and product grading are as follows: After the reaction was completed, the product was cooled, filtered, and washed three times with anhydrous ethanol to remove the physically adsorbed coupling agent. The resulting solid was vacuum dried at 80°C for 10 h. Finally, the dried powder was precisely classified using an air classifier, and the powder with a median particle size D50 of 2.0 μm was collected to obtain surface-modified red phosphorus.

[0036] Preparation Example 8 A β-cyclodextrin-encapsulated zinc borate is prepared as follows: Take 20g of β-cyclodextrin, add it to 200ml of deionized water, heat to 70℃ and stir until completely dissolved to obtain a saturated aqueous solution of β-cyclodextrin; Take 11g of ZB-233 type zinc borate (4ZnO·B2O3·H2O, D50=0.5μm), slowly add it to the above saturated aqueous solution of β-cyclodextrin, and stir continuously at 70℃ for 6h to fully encapsulate the host and guest components; After the reaction was completed, the mixture was naturally cooled to room temperature and then placed in a 4°C refrigerator for 20 hours to allow the inclusion complex to crystallize out. Collect the precipitate by vacuum filtration, and wash the precipitate twice each with 50 ml of anhydrous ethanol and 50 ml of deionized water to remove unencapsulated β-cyclodextrin and free zinc borate. The washed solid product was placed in a vacuum drying oven and dried at 45°C for 12 hours to constant weight. The dried product was then ground in a ball mill for 10 minutes and passed through a 400-mesh sieve. The median particle size D50 was controlled to be 2 μm to obtain β-cyclodextrin-included zinc borate.

[0037] Preparation Example 9 A β-cyclodextrin-encapsulated zinc borate is prepared as follows: Take 20g of β-cyclodextrin, add it to 200ml of deionized water, heat to 70℃ and stir until completely dissolved to obtain a saturated aqueous solution of β-cyclodextrin; Take 11g of FB-320 type zinc borate (2ZnO·3B2O3·3.5H2O, D50=0.5μm), slowly add it to the above β-cyclodextrin saturated aqueous solution, and stir continuously at 70℃ for 6h to fully encapsulate the host and guest components; After the reaction was completed, the mixture was naturally cooled to room temperature and then placed in a 4°C refrigerator for 20 hours to allow the inclusion complex to crystallize out. Collect the precipitate by vacuum filtration, and wash the precipitate twice each with 50 ml of anhydrous ethanol and 50 ml of deionized water to remove unencapsulated β-cyclodextrin and free zinc borate. The washed solid product was placed in a vacuum drying oven and dried at 45°C for 12 hours to constant weight. The dried product was then ground in a ball mill for 10 minutes and passed through a 400-mesh sieve. The median particle size D50 was controlled to be 2 μm to obtain β-cyclodextrin-included zinc borate.

[0038] Preparation Example 10 A β-cyclodextrin-encapsulated zinc borate, the difference being that the ZB-233 type zinc borate uses 6.0g.

[0039] Preparation Example 11 A β-cyclodextrin-encapsulated zinc borate, the difference being that the ZB-233 type zinc borate uses 7.3g.

[0040] Preparation Example 12 A β-cyclodextrin-encapsulated zinc borate, the difference being that the ZB-233 type zinc borate uses 14.6g.

[0041] Preparation Example 13 A β-cyclodextrin-encapsulated zinc borate, the difference being that the ZB-233 type zinc borate uses 17.5g.

[0042] Example 1 A low-gas-production red phosphorus flame-retardant reinforced PA66 composite material, the raw materials of which include PA66 resin, surface-modified red phosphorus, antioxidant, lubricant, surface-modified boron nitride, β-cyclodextrin-encapsulated zinc borate, metal passivator, nucleating agent, low-melting-point glass powder and chopped glass fiber.

[0043] The surface-modified red phosphorus was prepared in Preparation Example 3.

[0044] The antioxidant is a mixture of hindered phenolic antioxidant 1098 and phosphite antioxidant 168 in a mass ratio of 1:2.

[0045] The lubricant is ethylene bis-stearamide (EBS).

[0046] The metal passivating agent is N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine.

[0047] The nucleating agent is zinc phenylphosphonate.

[0048] The surface-modified boron nitride was prepared as in Preparation Example 1.

[0049] The zinc borate encapsulated with β-cyclodextrin was prepared in Preparation Example 8.

[0050] The preparation method of low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material is as follows: S1. Weigh 63.9 kg of PA66 resin, 5 kg of surface-modified red phosphorus, 0.4 kg of antioxidant, 0.4 kg of lubricant, 1.0 kg of surface-modified boron nitride, 1.0 kg of β-cyclodextrin-encapsulated zinc borate, 0.5 kg of metal passivator, 0.3 kg of nucleating agent, and 2.5 kg of low-melting-point glass powder and put them into a high-speed mixer. Mix at room temperature for 5 minutes to obtain a uniform premix. S2. The obtained premix is ​​fed into a co-rotating twin-screw extruder (length-to-diameter ratio L / D=44) through the main feed port. 25kg of chopped glass fiber is added in the middle section through the side feed port. The temperatures of each section of the extruder from the feeding section to the die head are set as follows: 240℃, 250℃, 255℃, 260℃, 260℃, 255℃. The main engine speed is set to 400rpm. The vacuum devolatilization device is turned on throughout the process (vacuum degree ≥-0.08MPa). After melt blending, the material is extruded, water-cooled, and pelletized to obtain composite material particles.

[0051] Comparative Example 1 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that it uses an equal mass of PA66 resin instead of surface-modified boron nitride, i.e., the raw material does not contain surface-modified boron nitride.

[0052] Comparative Example 2 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the surface modification with boron nitride was prepared in Example 2.

[0053] Comparative Example 3 A PA66 composite material, which differs from Example 1 in that it uses an equal mass of PA66 resin instead of modified red phosphorus, i.e., the raw material does not contain surface-modified red phosphorus.

[0054] Comparative Example 4 A PA66 composite material, which differs from Example 1 in that the surface-modified red phosphorus was prepared in Preparation Example 4.

[0055] Example 2 A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the surface-modified red phosphorus was prepared in Preparation Example 5.

[0056] Example 3 A low-gas-production red phosphorus flame-retardant reinforced PA66 composite material differs from Example 1 in that it uses an equal mass of PA66 resin instead of a metal passivating agent, i.e., the raw material does not contain a metal passivating agent.

[0057] Example 4 A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material differs from Example 1 in that it uses an equal mass of PA66 resin instead of a nucleating agent, i.e., the raw material does not contain a nucleating agent.

[0058] Example 5 A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material differs from Example 1 in that it uses an equal mass of PA66 resin instead of low-melting-point glass powder, i.e., the raw material does not contain low-melting-point glass powder.

[0059] Example 6 A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the surface-modified red phosphorus was prepared in Preparation Example 6.

[0060] Example 7 A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the surface-modified red phosphorus was prepared in Preparation Example 7.

[0061] Example 8 A low-gas-production red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the lubricant is oxidized polyethylene wax.

[0062] Example 9 A low-gas-production red phosphorus flame-retardant reinforced PA66 composite material differs from Example 1 in the amount of raw materials used. Specifically, it consists of 55 kg of PA66 resin, 4.5 kg of surface-modified red phosphorus, 0.3 kg of antioxidant, 0.3 kg of lubricant, 2 kg of surface-modified boron nitride, 1 kg of β-cyclodextrin-encapsulated zinc borate, 0.2 kg of metal passivator, 0.2 kg of nucleating agent, 1 kg of low-melting-point glass powder, and 20 kg of chopped glass fiber.

[0063] Example 10 A low-gas-production red phosphorus flame-retardant reinforced PA66 composite material differs from Example 1 in the amount of raw materials used. Specifically, it consists of 68 kg of PA66 resin, 5.5 kg of surface-modified red phosphorus, 0.45 kg of antioxidant, 0.5 kg of lubricant, 3 kg of surface-modified boron nitride, 1.5 kg of β-cyclodextrin-encapsulated zinc borate, 1 kg of metal passivator, 1 kg of nucleating agent, 3 kg of low-melting-point glass powder, and 35 kg of chopped glass fiber.

[0064] Example 11 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the β-cyclodextrin-encapsulated zinc borate was prepared in Preparation Example 9.

[0065] Example 12 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the β-cyclodextrin-encapsulated zinc borate was prepared in Preparation Example 10.

[0066] Example 13 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the β-cyclodextrin-encapsulated zinc borate was prepared in Preparation Example 11.

[0067] Example 14 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the β-cyclodextrin-encapsulated zinc borate was prepared in Preparation Example 12.

[0068] Example 15 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the β-cyclodextrin-encapsulated zinc borate was prepared in Preparation Example 13.

[0069] Example 16 A red phosphorus flame-retardant reinforced PA66 composite material, which differs from Example 1 in that the amount of β-cyclodextrin-encapsulated zinc borate is 0, that is, no β-cyclodextrin-encapsulated zinc borate is added.

[0070] The PA66 composite materials obtained in Examples 1-10 and Comparative Examples 1-3 were tested.

[0071] The testing content is as follows: Processing gas production Following ASTM E2058-22, accurately weigh 5.0 g of composite material particles as the test sample. The sample must be pre-dried under standard conditions to eliminate moisture interference; The sample is placed in a pressure-resistant, heatable, sealed reaction vessel connected to a precision pressure sensor and a gas collection and metering device, and filled with high-purity nitrogen to replace the air. The sealed container was heated to 265°C at a heating rate of 10°C / min and held at that temperature for 30 minutes. During this process, the red phosphorus-based component in the composite material particles was decomposed by heat, producing gases such as phosphine, which caused the pressure inside the container to rise. The pressure increase inside the container is monitored and recorded in real time using a calibrated pressure sensor. Based on the ideal gas law, the pressure increment is converted into the volume of gas produced under standard conditions (e.g., 0°C, 1 atm). Divide the measured total gas volume (unit: mL, converted to standard state) by the initial mass of the test sample (unit: g) to obtain the gas production per unit mass of the material under the test conditions, and the result is expressed in mL / g.

[0072] Vertical flammability rating Tested according to UL94.

[0073] Compared to the tracking index Tested in accordance with IEC 60112.

[0074] Tensile strength, flexural strength Tested in accordance with ASTM D790.

[0075] The test results are shown below.

[0076] Table 1. Results of gas production and vertical combustion rating in Examples 1-10 and Comparative Examples 1-3 Example 1 3.8 V-0 Example 2 4.5 V-0 Example 3 4.8 V-0 Example 4 4.1 V-0 Example 5 4.0 V-0 Example 6 4.3 V-0 Example 7 4.6 V-0 Example 8 3.9 V-0 Example 9 4.9 V-0 Example 10 4.0 V-0 Example 11 5.2 V-0 Example 12 4.5 V-0 Example 13 3.5 V-0 Example 14 3.8 V-0 Example 15 4.2 V-0 Example 16 5.8 V-0 Comparative Example 1 14.5 V-2 Comparative Example 2 9.2 V-1 Comparative Example 3 1.5 NR Table 2. Results of tracking index and mechanical properties of Examples 1-10 and Comparative Examples 1-3 Example 1 625 590 145 210 Example 2 610 560 142 205 Example 3 618 545 138 198 Example 4 620 580 135 192 Example 5 622 575 143 206 Example 6 615 570 141 202 Example 7 608 562 139 200 Example 8 623 588 144 208 Example 9 600 550 128 185 Example 10 628 595 148 215 Example 11 612 568 140 202 Example 12 618 582 142 205 Example 13 638 605 149 216 Example 14 626 592 146 211 Example 15 616 578 141 204 Example 16 605 555 138 198 Comparative Example 1 570 400 125 175 Comparative Example 2 590 480 130 182 Comparative Example 3 >600 >600 140 203 Comparing Example 1 and Comparative Examples 1-3, it can be seen that... Firstly, no surface-modified red phosphorus or other red phosphorus was added to Comparative Example 3, so its gas production was significantly low, and its flame retardant performance was poor.

[0077] Compared with Comparative Example 3, Comparative Example 1-2 showed improved flame retardant performance, but its detected gas production was significantly increased. This is because the surface-modified red phosphorus added in Comparative Example 1-2 was used as a flame retardant. However, the surface-modified red phosphorus in Comparative Example 1-2 had poor stability and was prone to decomposition and gas generation in processing and thermal environments.

[0078] Compared with Comparative Examples 1-3, Example 1 showed a significantly lower detected gas production rate than Comparative Examples 1-2, and the flame retardant performance of Example 1 was also improved compared with Comparative Examples 1-2.

[0079] Meanwhile, the initial CTI, CTI after aging, tensile strength, and flexural strength of Example 1 are all superior to those of Comparative Examples 1-3.

[0080] Therefore, in this application, KH550 is used to modify the surface of the coated red phosphorus to achieve physical isolation and inhibit its initial activity. Then, on this basis, nano boron nitride modified with octadecylamine is added. The surface-modified nano boron nitride serves as a multifunctional synergistic center, and at the same time plays a dual role as a "thermal conductor" and "barrier" for the surface-modified red phosphorus.

[0081] During processing and heating, nano-boron nitride, with its extremely high in-plane thermal conductivity, can quickly dissipate the "local hot spots" generated by the thermal oxidation of red phosphorus particles, inhibiting the generation of gases such as phosphine from the thermodynamic source and avoiding the generation of these gases during processing. When the material is used, nano-boron nitride is oriented within the PA66 matrix, forming a dense physical barrier network that effectively delays the penetration of external moisture and oxygen into the interior and the migration of internal acidic degradation products, thereby protecting the interface between the red phosphorus coating layer and the PA66 matrix and forming long-term electrical insulation stability (high CTI value). In addition, antioxidants and lubricants ensure the thermo-oxidative stability of the matrix and the processing fluidity of the overall system, making the material production process more uniform and stable, and ensuring the stability of material performance.

[0082] This achieves the suppression of gas generation during processing, while maintaining the excellent mechanical properties of the final material and preserving its long-term electrical stability.

[0083] Comparing Example 1 and Example 2, the detected gas production of Example 1 is less than that of Example 2, the initial CTI and the CTI after aging of Example 1 are greater than those of Example 2, and the tensile strength and flexural strength of Example 1 are greater than those of Example 2.

[0084] Therefore, boron-containing phenolic resin is used as the surface coating layer of red phosphorus in this application. This coating layer forms a dense and stable physical barrier on the surface of red phosphorus particles, which can effectively block the direct contact between water vapor, oxygen and the red phosphorus core, thereby significantly inhibiting the generation of phosphine gas caused by hydrolysis and oxidation of red phosphorus during storage, processing and use. Secondly, when the composite material is heated or burned, the boron-containing phenolic resin itself undergoes decomposition and cross-linking reaction to form boride, which promotes the formation of a denser, continuous and thermally stable expanded carbon layer. This carbon layer not only has excellent heat insulation and material insulation functions, but can also further encapsulate and fix red phosphorus, inhibiting its further decomposition and gas production. Thus, it produces a significant flame-retardant synergistic effect with red phosphorus decomposition products, PA66 matrix and boron nitride and other components, realizing a dual gas suppression mechanism of "physical sealing" and "chemical synergy", and improving the overall flame-retardant efficiency.

[0085] Comparing Example 1 and Example 3, the detected gas production of Example 1 is less than that of Example 3, the initial CTI and the CTI after aging of Example 1 are greater than those of Example 3, and the tensile strength and flexural strength of Example 1 are greater than those of Example 3.

[0086] Therefore, N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine is added as a metal passivating agent in this application, which can intervene in the specific catalytic pathway of thermo-oxidative degradation of PA66 polymer chains: The hydrazine structural unit of N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine can act as a polydentate ligand, exhibiting a strong complexing effect on trace amounts of transition metal ions (such as copper, iron, and manganese ions) within the material system and potentially introduced from the external environment, forming stable inert complexes, thereby causing them to lose their activity in catalyzing the oxidative chain scission reaction of PA66 molecular chains; the hindered phenolic structures at both ends of the N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]hydrazine molecule can directly capture alkyl free radicals generated under thermal or shearing conditions, and work together with antioxidants to block free radical chain reactions; This avoids the catalytic degradation that may be exacerbated by red phosphorus caused by trace metal impurities, thereby significantly inhibiting the resulting decrease in PA66 molecular weight, fluctuations in melt flow rate, and generation of small molecule volatiles, reducing gas production, and improving the stability of material mechanical properties and long-term electrical properties.

[0087] Comparing Example 1 and Example 4, the detected gas production of Example 1 is less than that of Example 4, the initial CTI and the CTI after aging of Example 1 are greater than those of Example 4, and the tensile strength and flexural strength of Example 1 are greater than those of Example 4.

[0088] Therefore, the system introduced in this application contains red phosphorus, glass fiber, and various fillers, which interfere with the crystallization integrity of the PA66 matrix. To address this, zinc phenylphosphonate is added as a nucleating agent, which provides a large number of highly ordered heterogeneous nucleation sites during the cooling process of the PA66 melt. This increases the crystallization initiation temperature of PA66, accelerates the crystallization rate, and promotes a significant refinement and more uniform distribution of spherulites. Ultimately, PA66 constructs a more dense and complete crystal structure at the microscopic level, thereby improving the mechanical properties and long-term electrical stability of the composite material. In addition, the faster and more complete crystallization process reduces the residence time of the melt at high temperatures, indirectly reducing the time window for the thermal oxidation of red phosphorus and reducing subsequent gas production.

[0089] Comparing Example 1 and Example 5, the gas production rate of Example 1 is less than that of Example 5, the tensile strength and flexural strength of Example 1 are greater than those of Example 5, and the initial CTI and the CTI after aging of Example 1 are greater than those of Example 5.

[0090] Therefore, this application incorporates low-melting-point glass powder into the composite material. When the material is exposed to open flame, extreme high-temperature environment, or arc erosion, the temperature exceeds the softening point of the glass powder, causing the low-melting-point glass powder particles to soften and melt, and flow and spread on the material surface to form a continuous, dense glassy covering layer with ceramic properties. The covering layer acts as an excellent heat insulation and oxygen barrier in the condensed phase, significantly hindering the transfer of external heat to the interior of the matrix and the outward overflow of internal flammable pyrolysis products, thereby inhibiting the continued combustion. On the other hand, its melt flow characteristics allow the covering layer to cover and fix any molten droplets that may be generated, improving flame retardant safety. Furthermore, the inorganic ceramic layer itself has extremely high insulation and arc resistance. Thus, it suppresses smoke generation during combustion and significantly enhances the surface's resistance to arc erosion.

[0091] Comparing Example 1 and Example 6-7, the detected gas production of Example 1 is less than that of Example 6-7, the initial CTI and the CTI after aging of Example 1 are greater than those of Example 6-7, and the tensile strength and flexural strength of Example 1 are greater than those of Example 6-7.

[0092] Therefore, in this application, it is preferable to control the size of the surface-modified red phosphorus at 1.0±0.05μm, as its synergistic effect with nano boron nitride is optimal, reducing gas generation during production and improving the material's processing and mechanical properties.

[0093] Comparing Example 1 and Example 8, the gas production rate of Example 1 is less than that of Example 8, the initial CTI and the CTI after aging of Example 1 are greater than those of Example 8, and the tensile strength and flexural strength of Example 1 are greater than those of Example 8. Therefore, ethylene bis-stearamide (EBS) has a better lubrication effect on the PA66 system with surface-modified red phosphorus and surface-modified boron nitride coexisting in this application, resulting in a higher melt extrusion molding rate and more stable product performance.

[0094] Comparing Examples 1 and 16, it can be seen that the detected gas production in Example 1 is less than that in Example 16. The initial CTI and the CTI after aging in Example 1 are both greater than those in Example 16. The tensile strength and flexural strength of Example 1 are also greater than those in Example 16. The only difference between Example 1 and Example 16 is that Example 1 added 1.0 part of β-cyclodextrin-encapsulated zinc borate (ZB-233 type), while Example 16 used an equal mass of PA66 resin, i.e., it did not contain β-cyclodextrin-encapsulated zinc borate. All other components, amounts, and preparation methods are completely identical.

[0095] The above data indicate that the addition of β-cyclodextrin-encapsulated zinc borate significantly reduces the processing gas production of the composite material, while simultaneously improving its electrical insulation stability and mechanical properties. The mechanism of action is as follows: β-cyclodextrin forms a host-guest inclusion complex with the BO / Zn-O groups on the surface of ZB-233 zinc borate through its hydrophobic cavities. The abundant hydroxyl groups on the outer edge of β-cyclodextrin form a hydrogen bond network with the PA66 amide bonds, the octadecylamine groups of surface-modified boron nitride, and the KH550 amino groups of surface-modified red phosphorus, ensuring uniform dispersion of ZB-233 particles in the matrix and preventing local agglomeration. During processing and use, the Zn sites on the ZB-233 surface can react with the free H3PO4 generated by red phosphorus hydrolysis to form a Zn3(PO4)2 ceramic phase, clearing the acidic driver of the autocatalytic cycle; simultaneously, its BO groups can absorb free water in the matrix (PA66 hygroscopic water, interfacial water), reducing the water supply required for red phosphorus hydrolysis. Therefore, β-cyclodextrin-encapsulated zinc borate, through the dual effects of "interfacial dispersion optimization + chemical acid removal and water absorption", effectively cuts off the autocatalytic cycle of red phosphorus hydrolysis without interfering with the flame-retardant main chain of the red phosphorus condensed phase (interfacial H3PO4 → polyphosphoric acid → char formation), thereby reducing the amount of PH3 produced and reducing the damage to the PA66 molecular chain caused by acid degradation, thus maintaining a higher CTI value and mechanical properties.

[0096] Comparing Example 1 and Example 11, it can be seen that the detected gas production in Example 1 is less than that in Example 11, the initial CTI and the CTI after aging in Example 1 are both greater than those in Example 11, and the tensile strength and flexural strength in Example 1 are both greater than those in Example 11.

[0097] The only difference between Example 1 and Example 11 is the type of zinc borate: Example 1 uses Preparation Example 8, and the zinc borate is type ZB-233; Example 11 uses Preparation Example 9, and the zinc borate is type FB-320.

[0098] The above data indicate that, under the same β-cyclodextrin inclusion process, ZB-233 zinc borate can more effectively reduce the processing gas production of composite materials compared to FB-320 zinc borate, while simultaneously improving electrical insulation stability and mechanical properties. The mechanism lies in the difference in chemical composition and crystal structure between the two types of zinc borate, leading to different acid-absorbing and water-absorbing efficiencies in the matrix. ZB-233 zinc borate has the chemical formula 4ZnO·B₂O₃·H₂O, with a ZnO to B₂O₃ molar ratio of 4:1, containing more ZnO active sites per unit mass; while FB-320 zinc borate has the chemical formula 2ZnO·3B₂O₃·3.5H₂O, with a ZnO to B₂O₃ molar ratio of 2:3, and a relatively lower ZnO content. In the process of inhibiting the autocatalytic cycle of red phosphorus hydrolysis, ZnO is the core component for removing free H3PO4 (3ZnO + 2H3PO4 → Zn3(PO4)2 + 3H2O). The higher the ZnO content, the stronger the acid removal ability and the higher the efficiency of interrupting the autocatalytic cycle. Although the FB-320 type contains more B2O3 (with strong water absorption capacity), the gas production in Example 11 is actually higher, indicating that acid removal (the driver for interrupting the autocatalytic cycle) is more critical than water absorption—once free H3PO4 is removed in time, the autocatalytic cycle is blocked, the red phosphorus hydrolysis rate drops significantly, and the gas production naturally decreases. In addition, the crystal structure of ZB-233 type zinc borate may have a better geometric match with the β-cyclodextrin cavity than the FB-320 type, which is conducive to the formation of a more stable host-guest inclusion complex, making the inclusion product more uniformly dispersed in the matrix, and further improving the accessibility of Zn sites. Therefore, this application selects ZB-233 type zinc borate as the core material for β-cyclodextrin inclusion, which has non-obvious advantages over conventional FB-320 type zinc borate in terms of gas generation suppression and overall performance.

[0099] Comparing Examples 1 and 12-15, it can be seen that the detected gas production of Example 1 is less than that of Examples 12 and 15, the same as that of Example 14, and slightly greater than that of Example 13; the initial CTI and the CTI after aging of Example 1 are between those of Examples 13 and 14, and both are greater than those of Examples 12 and 15; the tensile strength and flexural strength of Example 1 are between those of Examples 13 and 14, and both are greater than those of Examples 12 and 15. The only difference between Example 1 and Examples 12-15 is the different molar ratio of β-cyclodextrin to ZB-233 type zinc borate.

[0100] The above data indicate that the molar ratio of β-cyclodextrin to ZB-233 zinc borate has a significant impact on the gas generation suppression effect and overall performance of the composite material, and there exists an optimal window (1:1~1:2). When the molar ratio falls within this range (Examples 1, 13, 14), the gas generation remains at a low level of 3.5~3.8 mL / g, while CTI and mechanical properties are both in the high range; when the molar ratio exceeds this range, the gas generation increases to 4.2~4.5 mL / g, and CTI and mechanical properties decrease simultaneously. The mechanism is that the molar ratio of β-cyclodextrin to ZB-233 directly affects the structural integrity and dispersion uniformity of the inclusion complex. When the molar ratio is 1:1 to 1:2, the cavity of β-cyclodextrin can form a stable host-guest inclusion complex with the BO / Zn-O groups on the surface of ZB-233. The inclusion layer is uniform and dense. Through the hydrogen bond network between the hydroxyl groups on the outer edge of β-cyclodextrin and the PA66 matrix, the surface-modified boron nitride, and the surface-modified red phosphorus, the ZB-233 particles are uniformly dispersed in the matrix. Its Zn sites can efficiently remove free H3PO4 generated by red phosphorus hydrolysis, and the BO groups effectively absorb free water, thereby maximally inhibiting the autocatalytic cycle of red phosphorus hydrolysis. Therefore, controlling the molar ratio of β-cyclodextrin to ZB-233 type zinc borate within the range of 1:1 to 1:2 is a key technical parameter for achieving the optimal dispersion state and acid-removing and water-absorbing efficiency of β-cyclodextrin-encapsulated zinc borate. This narrow range limitation has a non-obvious synergistic optimization effect.

[0101] In conjunction with Examples 1 and 9-10, the detected gas production of Examples 1 and 9-10 is less than that of Comparative Examples 1-2, the initial CTI and the CTI after aging of Examples 1 and 9-10 are greater than those of Comparative Examples 1-2, and the tensile strength and flexural strength of Examples 1 and 9-10 are greater than those of Comparative Examples 1-2.

[0102] Therefore, the range of composite material raw material usage in this application is 55-68 parts of PA66 resin. The red phosphorus flame-retardant reinforced PA66 composite material obtained by using 4.5-5.5 parts of surface-modified red phosphorus, 20-35 parts of chopped glass fiber, 0.3-0.5 parts of antioxidant, 0.3-0.5 parts of lubricant, 1-3 parts of surface-modified boron nitride, 0.2-1 parts of metal passivator, 0.2-1 parts of nucleating agent, and 1-3 parts of low-melting-point glass powder has low gas production and stable performance.

[0103] This specific embodiment is merely an explanation of the present invention and is not intended to limit the present invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but as long as they are within the scope of protection claimed by the present invention, they are protected by patent law.

Claims

1. A low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material, characterized in that, The following components are included by mass parts: 55-68 parts of PA66 resin; 4.5-5.5 parts of surface-modified red phosphorus; the surface-modified red phosphorus is coated red phosphorus modified with silane coupling agent KH550; 20-35 parts chopped glass fiber; Antioxidant 0.3-0.5 parts; 0.3-0.5 parts lubricant; 1-3 parts of surface-modified boron nitride; the surface-modified boron nitride is nano-sized boron nitride modified with octadecylamine.

2. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, The coating layer is a boron-containing phenolic resin.

3. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, It also contains 0.5-1.5 parts of β-cyclodextrin-encapsulated zinc borate, wherein the zinc borate is 4ZnO·B2O3·H2O (ZB-233 type), and the molar ratio of β-cyclodextrin to zinc borate is 1:1 to 1:

2.

4. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, It also includes 0.2-1 parts of a nucleating agent, wherein the nucleating agent is zinc phenylphosphonate.

5. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, It also includes 1-3 parts of low-melting-point glass powder, wherein the low-melting-point glass powder is borosilicate glass powder.

6. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, The median particle size D50 of surface-modified red phosphorus is 1.0 ± 0.05 μm.

7. The low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material according to claim 1, characterized in that, The lubricant is ethylene bis-stearamide.

8. A method for preparing a low-gas-yield red phosphorus flame-retardant reinforced PA66 composite material as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Ingredients and premixing: Weigh each component according to the stated weight percentage, and mix all components in a high-speed mixer for 3-5 minutes to obtain a premix; S2. Melt blending and granulation: The premixed material is added to the main feed port of a twin-screw extruder, and the chopped glass fiber is added through the side feed port. The vacuum devolatilization device is turned on. After melt blending, extrusion, water cooling and pelletizing, composite material particles are obtained.